IMPLEMENTASI KEBIJAKAN ANTISIPASI DAN PENANGANAN BANJIR KOTA SAMARINDA - joni sinatra ginting (Magister Administrasi Publik FISIP Universitas Mulawarman, 2022)
Abstract: This study aimed to analyze the implementation of the Samarinda City Flood Anticipation and Handling Policy based on the 2021-2026 RPJMD. And to identify what are the inhibiting and supporting factors. This research is a descriptive qualitative approach that aims to describe the implementation of flood control policies in Samarinda City. This research will obtain information about how the program’s performance is carried out through this research.The results showed that the Samarinda City Flood Anticipation and Handling Policy in the communication aspect had been carried out well and understood by all components and increased public awareness in participating in the policy. The policy has been implemented optimally in the sort of resources but is stilartnstrained by financial resources. In Respect of dis, that by the leadthatactor’s en carried out well and has become capital. There is support from all stakeholders/actor policies for anticipating and handling floods in Samarinda City. In the organizational structure formed based on their respective roles, SOPs in response have also been made. When disaster strikes. Strengthening the roles and responsibilities of OPD has also been attached to their units in the event of a disaster. Meanwhile, the inhibiting factors, namely the existence of territorial barriers, limited land in some areas to build retention ponds—inadequate funding/financial factors in accelerating flood prevention. Then the supporting element is the support from the community, the Provincial Government, and the Central Government in implementing the policy. Keywords: Policy Implementation, Flood, Samarinda.